Reduced interocular suppression after inverse patching in anisometropic amblyopia - Hu, Jingyi; Chen, Jing; Ku, Yixuan; Yu, Minbin (Frontiers in Neuroscience, 2023)
Purpose: In recent investigations, Lunghi et al. (2018) and Zhou et al. (2019) observed substantial enhancements in binocular balance, visual acuity, and stereovision among older children and adults with amblyopia by patching the amblyopic eye (i.e., inverse patching) for 2 hours daily over 2 months. Despite these promising findings, the precise neural mechanisms underlying inverse patching remain elusive. This study endeavors to delve deeper into the neural alterations induced by inverse patching, focusing on steady-state visual evoked potentials (SSVEPs). We specifically investigate the changes in SSVEPs following monocular deprivation of either the fellow eye or the amblyopic eye in older amblyopic children and adults. Method: Ten participants (17.60±2.03 years old; mean±SEM), clinically diagnosed with anisometropic amblyopia, were recruited for this study. Each participant underwent a 120-minute patching session on their fellow eye on the first day, followed by a similar session on their amblyopic eye on the second day. Baseline steady-state visual evoked potentials (SSVEPs) measurements were collected each day prior to patching, with post-patching SSVEPs measurements obtained immediately after the patching session. The experimental design incorporated a binocular rivalry paradigm, utilizing SSVEPs measurements. Results: The results revealed that inverse patching induced a heightened influence on neural plasticity, manifesting in a reduction of interocular suppression from the fellow eye to the amblyopic eye. In contrast, patching the fellow eye demonstrated negligible effects on the visual cortex. Furthermore, alterations in interocular suppression subsequent to inverse patching exhibited a correlation with the visual acuity of the amblyopic eye. Conclusion: Inverse patching emerges as a promising therapeutic avenue for adolescents and adults grappling with severe anisometropic amblyopia that proves refractory to conventional interventions. This innovative approach exhibits the potential to induce more robust neural plasticity within the visual cortex, thereby modulating neural interactions more effectively than traditional amblyopia treatments.